(untitled) (CIPEEX, 2025)
CHILDBIRTH AND LEARNING: THE ROLE OF A MEDICAL STUDENT ON THE FRONTLINE This article details the prenatal care and delivery experience of a medical student in Anápolis, Goiás. The descriptive study looked at the student’s involvement in a real-world care setting. She considered the difficulties and intricacies of conception, pregnancy, and labor, fusing her personal experiences with the theoretical and scientific understanding she had received during her academic education. This third-time mother has had normal deliveries and miscarriages in the past. She was eager for her second daughter to arrive and diligently followed all Unified Health System (SUS) requirements during the antenatal care period. But around 34 weeks of pregnancy, a dangerous issue developed when the patient started to bleed following intense exercise. She was being watched carefully by the student, who suggested right away that she consult a specialist. Afterwards, examinations revealed a ruptured blood vessel in the perianal area, which fortunately did not pose a serious threat to the mother or baby. The birth process is well described in the paper, which also emphasizes the student’s crucial involvement at this crucial time. The woman returned to the hospital with the onset of labor at 41 weeks of pregnancy. At first, it was suggested that she stay at home and wait for developments. Her cervix was found to be 6 cm dilated when she returned to the delivery room with frequent, strong contractions. She was uncomfortable and apprehensive because the hospital once more advised her to wait rather than induce birth. The student demonstrated amazing initiative and planning throughout the birth. She went with the woman to the bathroom and, seeing that the birth was going to happen soon, she took the crucial choice to assist. The baby’s amniotic sac was still whole. In addition to supporting the woman and giving crucial advice, the student delivered the kid safely and waited for help to come. This incident made clear how crucial it is for aspiring doctors to receive extensive training and real-world experience, as theoretical knowledge cannot be applied in emergency scenarios. The experiences detailed in this story highlight the necessity of a thorough, patient-centered approach to conception and delivery. The prompt and efficient interventions by the students underscore the vital significance of possessing a comprehensive comprehension of the pregnancy process and the ability to take decisive action when necessary to safeguard the safety and welfare of the mother and child. In addition, the report emphasizes the need for effective communication between healthcare providers and patients, and the need to continually review and improve hospital treatment protocols, with a focus on the human touch and the quality of care provided.